2001
DOI: 10.1007/bf03036430
|View full text |Cite
|
Sign up to set email alerts
|

Natural occurrence of aflatoxin B1 in some Indonesian food and feed products in Yogyakarta in year 1998–1999

Abstract: A survey was conducted between 1998-1999 to evaluate the level of aflatoxin B1 (AfB1) contamination in some selected Indonesian food products, mainly peanuts and peanut products for sale in supermarkets or traditional markets in Yogyakarta, Indonesia. Quantitative analysis was carried out on 118 samples using the ELISA (Enzyme-Linked Immunosorbent Assay) technique. The results indicate that (61.1%) samples were contaminated with AfB1 at range 2.0 to 249.0 μg/kg. Approximately 50% of the baby food products anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Another survey covered 20 states of India, reported that AFB 1 was present in 814 of 1200 samples ranging from 0.1 to 308 μg/kg [46]. In Indonesia, AFB 1 was detected in 2 of 2 rice samples with a range between 2.0–7 0.0 μg/kg [47]. Some studies have been conducted in Iran to monitor aflatoxin in rice and rice products.…”
Section: Introductionmentioning
confidence: 99%
“…Another survey covered 20 states of India, reported that AFB 1 was present in 814 of 1200 samples ranging from 0.1 to 308 μg/kg [46]. In Indonesia, AFB 1 was detected in 2 of 2 rice samples with a range between 2.0–7 0.0 μg/kg [47]. Some studies have been conducted in Iran to monitor aflatoxin in rice and rice products.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, A. flavus is a common producer of aflatoxin B, causing pre-and post-harvest agricultural stuff contamination (Klich, 2007). The contamination is mainly dominated by aflatoxin B1 (AFB1) (Noviandi et al, 2001), and thus AFB1 would be the center concern in animal and human public health.…”
Section: Introductionmentioning
confidence: 99%
“…In Indonesia, aflatoxins are frequently found in agriculture commodities and their derivatives [4][5]. In addition, residue and its metabolites are also obtained in husbandry products such as milk [6][7], eggs [8], and chicken meat [9].…”
Section: Introductionmentioning
confidence: 99%